Impact of the Acid Value of Vietnam Rubber Seed Oil on an Epoxidation - Nguyen, Thi Thuy; Vu, Minh Duc; Nguyen, Thanh Liem (Old Journal, 2017)
Besides triglycerides, Vietnam rubber seed oil contains a high amount of free fatty acids which make it dififcult to preserve and take part in a chemical modification. [cite: 9] An esterification is one of many methods to reduce the acid value of the oils by converting the free fatty acids to methyl esters. [cite: 10] Furthermore, this process do not change a composition of unsaturated componds in oils. [cite: 11] It was found that the esterified oils have the acid value in the range of 47.6 to 1.12 mgKOH/g with different reaction time. [cite: 12] Effect of the acid value of the oils on the epoxidation process is studied through a double bond conversion, an epoxidaiton yield and the oxirane content of an epoxidized oil. [cite: 13] When the acid value of the oil reactant was above 4.98 mgKOH/g, the epoxidation yield increased with decreasing the acid value of the oil. [cite: 14] However, when the acid value of the oil reactant was lower than 4.98 mgKOH/g, the epoxidation yield has almost no change if the acid value of the oil further declines. [cite: 15]